Realizing the promise of neglected and underutilized species: Policy Brief - Bioversity International; Rudebjer, P.G.; Meldrum, G.; Padulosi, S.; Hall, R.; Hermanowicz, E. (Bioversity International, 2014)
Drawing on the lessons learned from the 3rd International Conference on Neglected and Underutilized Species (NUS) in September 2013 in Ghana and other recent initiatives, this policy brief highlights key roles of NUS in addressing five critical development challenges: conservation of agricultural biodiversity; agricultural and rural development; climate change; food and nutrition security; and gender, culture and empowerment of women. The need for capacity development in NUS is also stressed. Recommendations and key actions indicate ways forward to mainstream NUS into policies and programmes at national, regional and international levels.